Immunogenicity of H5N1 influenza vaccines in elderly adults: a systematic review and meta-analysis. Issue 2 (1st February 2021) - Zhang, Ke; Wu, Xiaoxue; Shi, Yu; Gou, Xiaoqin; Huang, Junqiong
ABSTRACT: Several different vaccines have been produced for human use to prevent the highly pathogenic H5N1 influenza. Some studies reported that the clinical effectiveness of influenza vaccines in older adults may be lower than in younger adults. In this study, a meta-analysis of the immunogenicity of H5N1 influenza vaccines in elderly adults was performed. Database search was conducted in EMBASE, PubMed, the Cochrane Library, Chinese VIP, Wanfang and CBM. A total of 3951 elderly adults from 10 articles were included in the meta-analysis. Compared to a single dose, two doses of H5N1 vaccines resulted in the higher seroconversion and seroprotection. For all groups treated with adjuvanted vaccines, there were significant increases (1.55- to 2.16-fold) in the seroconversion rates (SCRs) and seroprotection rates (SPRs) after two immunizations. Oil-in-water emulsion (OE)-adjuvanted 7.5 μg vaccine caused higher antibody responses than 3.75 μg of vaccine (SCR: risk ratio (RR) = 1.26 (1.19, 1.33); SPR: RR = 1.25 (1.14, 1.36)). Elderly adults exhibited slightly lower antibody responses only when given 7.5 μg of OE-adjuvanted vaccine (SCR: RR = 1.06 (1.01, 1.11)) than younger adults. After treatment with the 7.5 μg of OE-adjuvanted vaccines, the most commonly reported adverse events were injection site pain, swelling and erythema, with the incidence of 32%, 3% and 2%, respectively, and no serious adverse events were found. These data demonstrate that two doses of 7.5 µg of OE-adjuvanted H5N1 vaccine are well tolerated and induce a robust antibody response in elderly adults.